2019
DOI: 10.1080/23299460.2019.1633227
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful collaboration for responsible innovation

Abstract: Many innovative businesses have discovered an added value in collaborating with experts, users or other stakeholders in developing innovative products or services. Not all collaboration with stakeholders, however, corresponds to the criteria for opening up an innovation process to the needs of societal actors under the terms of responsible innovation. The question of what makes collaboration meaningful in the sense of responsible innovation was presented and discussed in a 75 min workshop at the European Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 5 publications
(7 reference statements)
0
17
0
1
Order By: Relevance
“…RI research revolves around whether and how to lead technology and innovation to socially desired goals [10] and manage innovation through early "upstream" interventions rather than post-event "downstream" monitoring and "corrective" interventions [11]. Its core is the process of open research and innovation, which incorporates "new voices of science and innovation governance" [12]; on the one hand, it aims to improve the legalization and democratization of the innovation process and output, and on the other hand, it attempts to increase the diversity of views to meet the needs of social actors [13]. To meet these needs, RI focuses on the participation and collaboration of stakeholders [14]; they need to continue to participate, not only in consultation, but also to provide information, power, and opportunities to play a role in decision-making to achieve what is called "mutually beneficial interaction" [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RI research revolves around whether and how to lead technology and innovation to socially desired goals [10] and manage innovation through early "upstream" interventions rather than post-event "downstream" monitoring and "corrective" interventions [11]. Its core is the process of open research and innovation, which incorporates "new voices of science and innovation governance" [12]; on the one hand, it aims to improve the legalization and democratization of the innovation process and output, and on the other hand, it attempts to increase the diversity of views to meet the needs of social actors [13]. To meet these needs, RI focuses on the participation and collaboration of stakeholders [14]; they need to continue to participate, not only in consultation, but also to provide information, power, and opportunities to play a role in decision-making to achieve what is called "mutually beneficial interaction" [13].…”
Section: Introductionmentioning
confidence: 99%
“…Its core is the process of open research and innovation, which incorporates "new voices of science and innovation governance" [12]; on the one hand, it aims to improve the legalization and democratization of the innovation process and output, and on the other hand, it attempts to increase the diversity of views to meet the needs of social actors [13]. To meet these needs, RI focuses on the participation and collaboration of stakeholders [14]; they need to continue to participate, not only in consultation, but also to provide information, power, and opportunities to play a role in decision-making to achieve what is called "mutually beneficial interaction" [13]. Meanwhile, this inclusiveness of upstream stakeholders and the public can help achieve collective responsibility to control and guide innovation so that it is ethically acceptable, societally desirable, and sustainable [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…There are always agencies that initiate and facilitate co-creation, and there is action needed from relevant actors for taking up the outcomes of the co-creation activity. This predefined ownership might influence the distribution of power and thereby negatively influence the collaboration between stakeholders in the cocreation process (Jarmai & Vogel-Pöschl, 2020). Furthermore, we found that adaptation is easier to achieve in an early developmental stage of the technology, as there is still room for adjustment than in a later stage, and anticipating societal needs values is easier in an application-oriented workshop.…”
Section: Main Findingsmentioning
confidence: 81%
“…However, this comes at the cost of inclusion, which is needed for a legitimate innovation trajectory, because it gives the stakeholder a certain power over the other stakeholders. Earlier research has already concluded that an inclusive and adaptive innovation process inevitably leads to the question of power (Jarmai & Vogel-Pöschl, 2020;Stilgoe et al, 2013). There are always agencies that initiate and facilitate co-creation, and there is action needed from relevant actors for taking up the outcomes of the co-creation activity.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation